Social insurance as a mechanism for minimizing the income gap between workers: comparative analysis and European experience - Denys A. Puntus; Mykola P. Kucheryavenko; Oleg M. Yaroshenko; Yaroslav O. Kostohryz; Anzhelika O. Tkachuk (Población y Salud en Mesoamérica)
Introduction: The aim of this study is to determine the extent to which social insurance can reduce income inequality among workers. This study explores the role of social insurance as a tool for minimizing income inequality among workers. Methodology: The study adopts a comparative approach to examining differences in social insurance systems in Norway, the Netherlands, Germany, Latvia, Romania, and Bulgaria. By comparing the selected countries, the research examines the correlation between the level of social insurance and the disparity in workers' incomes. Results: The analysis identifies key indicators such as social insurance expenditures as a percentage of GDP, population coverage, minimum wage levels, and the Gini index to evaluate the effectiveness of social insurance systems. The findings highlight significant differences in how social insurance is implemented and its impact on income distribution across these countries. In particular, the study provides insights into the mechanisms through which social insurance can mitigate economic inequality and offers a comprehensive understanding of the strengths and weaknesses of various social insurance models. Conclusions: This detailed examination allows for a nuanced comparison that can inform policy decisions and improvements in social insurance practices aimed at achieving greater economic equality and social justice. By analyzing different models and approaches within the selected countries, the study seeks to identify best practices and provide recommendations for policy improvements in social insurance systems.